Effect Of Arsenic On Pancreas With Special Emphasis Of Glucose Metabolism (Applied Biological Research, 2023)
The increasing human interventions have significantly contributed to the environmental pollution, especially due to heavy metal and metalloid exposure  including toxic non-essential elements like arsenic. Arsenic is a potent endocrine disruptor and may adversely affect human health. This study was  aimed to assess the detrimental effects of arsenic using Swiss albino mice as a  model and postulate the mechanisms behind the harmful effects of arsenic on  the structural integrity of pancreas, hormone levels, and downstrmetabolic parameters. The effects of arsenic on the structural and hormonal  (insulin and glucagon) status of pancreas in mice was determined by observing changes through histological, SEM, and ELISA methods. Alterations in  glucose metabolism, with special emphasis on blood glucose and liver glycogen  levels, was observed by biochemical estimation and also by examining the role  of arsenic in oxidative stress by anti-oxidant enzyme assay. The results  revealed that arsenic caused disintegration and degeneration of exocrine andendocrine parts of pancreas. Arsenic decreased insulin and amylase levels and  increased glucagon levels. It decreased anti-oxidant enzymes, which may cause  an increase in blood glucose with simultaneous decrease in liver glycogen. It is concluded that arsenic induces structural and hormonal alterations in pancreas, which increases blood glucose and alters glucose homeostasis which leads to stress in the animal physiology.
Keywords: Anti-oxidant; ELISA; endocrine disruptor; insulin; stress